2009
DOI: 10.1007/s00044-009-9206-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity studies of furan derivatives

Abstract: The organic compounds, 4-Ethyl-2synthesized and purified through column chromatography and preparative TLC. All compounds were characterized by IR, 1 H, 13 C NMR, MS, and microanalysis. The in vitro antibacterial and antifungal activities of these compounds were investigated against some bacteria and fungi. The antibacterial and antifungal activities were measured by using the disc-diffusion method against gram-positive bacteria, i.e., Staphylococcus aureus ATCC 25923, Staphylococcus enteritidis ATCC1376, Psyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…10,[20][21][22][23][24] Manganese(III) acetate dihydrate (98%) was prepared using an electrochemical method according to the literature. 25 All compounds were purified through column chromatography or preparative TLC and characterized by IR, 1 H-NMR, 13 C-NMR, 19 F-NMR, HMBC, NOSY, LC/MS, and microanalysis. Melting points were determined using a Gallenkamp capillary melting point apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,[20][21][22][23][24] Manganese(III) acetate dihydrate (98%) was prepared using an electrochemical method according to the literature. 25 All compounds were purified through column chromatography or preparative TLC and characterized by IR, 1 H-NMR, 13 C-NMR, 19 F-NMR, HMBC, NOSY, LC/MS, and microanalysis. Melting points were determined using a Gallenkamp capillary melting point apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…IR spectra (KBr disc) were obtained with a Matson 1000 FTIR spectrometer in the 400-4000 cm -1 range with 4cm -1 resolution. 1 H-NMR, 13 C-NMR and 19 F-NMR spectra were recorded on a Bruker DPX-400 MHz High Performance Digital FT-NMR spectrometer. The mass spectra were measured on a Micromass UK Platform II spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also recently reported that some 3-cyano-4,5-dihydrofurans show antifungal and antibacterial activities. 21 Lunacrine, bucharaminol, acrophylline, dicramnine, isotaifine, araliopsine, almein, and oligophylidine are quinoline alkaloids commonly found in nature. It is reported that these compounds show antiparasitic, anthelmintic, cytotoxic, antiarrhythmic, spasmolytic, sedative, antitumor, and antimalarial activities.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of furan derivatives has engrossed substantial attention from organic and medicinal chemists for many years as they belong to a class of compounds with proven utility in medicinal chemistry 10 . Furan derivatives are known to be associated with multiple biological activities 11,12 . Therefore, both the pyrimidine and furan possess worthy and imperative bioactivities, which render them useful substances in drug research.…”
Section: Introductionmentioning
confidence: 99%